Biological activity of PANI–tetrazole and PANI–pyrazole composites against microbial strains - Purnima Chaubisa; Dharmendra Dharmendra; Yogeshwari Vyas; Priyanka Chundawat; Charul Paliwal; Chetna Ameta (Discover Chemistry)
Abstract In the present work, we have completely synthesized PANI–tetrazole and PANI–pyrazole composites via chemical oxidative polymerization, using tosic acid (C7H8O3S) and ammonium persulphate ((NH4)2S2O8). The characterization of these synthesized composites was achieved using gel permeation chromatography (GPC), Fourier Transform Infrared (FTIR), proton nuclear magnetic resonance (1H-NMR), and thermo-gravimetric analysis (TGA) techniques. The structural characterization with 1H-NMR and FT-IR techniques confirmed that the development of emeraldine salt form of PANI by the detected peaks of PANI and its synthesized composites. The GPC technique used for calculation of the molecular weight of the synthesized composites, including PANI, PANI–tetrazole and PANI–pyrazole composites. The anti-bacterial activity examined against pathologically significant bacteria Staphylococcus aureus and Streptococcus pyogenus a remarkable efficacy of minimum inhibitory concentration (MIC) for the PANI–pyrazole composite when related with other synthesized composite. The PANI–tetrazole composite exhibited superior anti-fungal activity against Aspergillus niger, and Aspergillus clavatus, surpassing that of individual PANI. Furthermore, an exploration into the anti-TB activity of the PANI–pyrazole composite against Mycobacterium tuberculosis H37RV with an MIC value of 0.25 µg/mL. A greater and positive MIC exhibited with the synthesized PANI–tetrazole and PANI–pyrazole composites confirms their potential applications as a useful anti-bacterial, anti-fungal and anti-tuberculosis agent.